2020
DOI: 10.1098/rsos.191461
|View full text |Cite
|
Sign up to set email alerts
|

Network-based protein structural classification

Abstract: Experimental determination of protein function is resource-consuming. As an alternative, computational prediction of protein function has received attention. In this context, protein structural classification (PSC) can help, by allowing for determining structural classes of currently unclassified proteins based on their features, and then relying on the fact that proteins with similar structures have similar functions. Existing PSC approaches rely on sequence-based or direct three-dimensional (3D) structure-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 82 publications
(159 reference statements)
1
25
0
Order By: Relevance
“…PDMs may be generated from the distances between different selections of atoms, including the alpha (C α ) and/or beta (C β ) carbons of the polypeptide backbone, or the heavy (non-hydrogen) atoms of the backbone and side-chains. The relative merits of different representations remain disputed: Duarte et al (2010) concluded that a combination of C α and C β atoms outperforms individual components (and particularly C α ) when reconstructing 3D protein structures from contact maps, whilst C α maps performed better than sidechain geometric centres for enzyme class prediction in a study by Da Silveira et al (2009), and heavy atom representations performed well in a more recent publication from Newaz et al (2020).…”
Section: Representing Proteins As Images: Protein Distance Mapsmentioning
confidence: 99%
See 3 more Smart Citations
“…PDMs may be generated from the distances between different selections of atoms, including the alpha (C α ) and/or beta (C β ) carbons of the polypeptide backbone, or the heavy (non-hydrogen) atoms of the backbone and side-chains. The relative merits of different representations remain disputed: Duarte et al (2010) concluded that a combination of C α and C β atoms outperforms individual components (and particularly C α ) when reconstructing 3D protein structures from contact maps, whilst C α maps performed better than sidechain geometric centres for enzyme class prediction in a study by Da Silveira et al (2009), and heavy atom representations performed well in a more recent publication from Newaz et al (2020).…”
Section: Representing Proteins As Images: Protein Distance Mapsmentioning
confidence: 99%
“…A review of the literature was conducted to identify historic approaches to PSC, detailed in Appendix Table A1. Three broad methodologies were encountered: those in which traditional machine learning algorithms were applied to features extracted from PDMs (Shi and Zhang, 2009;Taewijit and Waiyamai, 2010;Vani and Kumar, 2016;Pires et al, 2011); a second set training deep CNNs directly on large datasets of maps (Sikosek, 2019;Eguchi and Huang, 2020); and ensemble models combining different approaches (Zacharaki, 2017;Newaz et al, 2020). Studies relying on features derived from amino acid sequence alone are not listed exhaustively, however state of the art is included in Table A1 for completeness (Xia et al, 2017;Hou et al, 2018).…”
Section: Related Work: Protein Structure Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has generally been argued that the topology of complex networks represent their underlying generative phenomena and there exist inherent similarity along with unique characteristic features among networks of different domains that can be leveraged to discriminate between them (12,13). Characterizing networks using these features have been reported for both within domain (category) (14) or different domain networks (15) using microscopic (e.g. degree), mesoscopic (e.g.…”
Section: Introductionmentioning
confidence: 99%